National Service for Health : the Labour Party's post-war policy (London : Labour Party)
1943-04 1943 1940s 24 pages THE LABOUR PARTY NATIONAL SERVICE FOR HEALTH The Labour Party's Post-war Policy PRICE TWOPENCE Transport House, Smith Square, London, S.W.1 36/H24/40